2002
DOI: 10.1159/000064930
|View full text |Cite
|
Sign up to set email alerts
|

Education, Occupation, and Prevalence of Dementia: Findings from the Conselice Study

Abstract: Information about the epidemiology of dementia in Italy is still limited, although this cognitive disorder represents a serious public health concern. We estimated the prevalence of dementia and dementia subtypes in the elderly population of a Northern Italian municipality, Conselice, in the Emilia Romagna region (n = 1,016 subjects aged 65–97 years). The associations of dementia with two modifiable risk factors, education and occupation, were also evaluated. Overall dementia prevalence was 5.9% (95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
61
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 37 publications
(89 reference statements)
11
61
1
3
Order By: Relevance
“…Cross et al 2013 in an article also showed a low level of education was associated with the occurrence of a NCD [36]. These findings corroborate the studies already conducted in the general population on dementia [40]- [42]. Thus, the low educational level reduces, in addition to the neuronal degeneration induced by the virus, neuronal plasticity phenomenon that would protect against dementia [43] [44].…”
Section: Education Levelsupporting
confidence: 80%
“…Cross et al 2013 in an article also showed a low level of education was associated with the occurrence of a NCD [36]. These findings corroborate the studies already conducted in the general population on dementia [40]- [42]. Thus, the low educational level reduces, in addition to the neuronal degeneration induced by the virus, neuronal plasticity phenomenon that would protect against dementia [43] [44].…”
Section: Education Levelsupporting
confidence: 80%
“…Ce résultat a été retrouvé lors d'études antérieures réalisées dans le monde. En Italie, Ravaglia et al [29] ont trouvé auprès d'une population de 1016 personnes âgées de 65 à 97 ans et plus réparties selon leur niveau d'instruction des prévalences de 29,3%, 9,7%, 2,1% respectivement chez les populations ayant fait 0 à 1 an d'étude, 2 à 3 ans d'étude et plus de 3 ans d'étude. Prencipe et al [27], lors d'une étude transversale menée dans trois villages d'Italie du centre, ont étudié la prévalence de la démence dans une population de 968 personnes âgées de plus de 64 ans habitant dans la zone.…”
Section: Discussionunclassified
“…Brain Ageing (CSBA) is a populationbased prospective survey with the main aim of exploring dementia epidemiology and risk factors in the elderly (14). After approval by our institutional review board, written informed consent was obtained from all participants.…”
Section: Research Design and Methods -The Conselice Study Ofmentioning
confidence: 99%
“…Except for dementia, diagnosed through a standardized workup (14), the other diagnoses were based on self-report and information from the participant's general practitioner. BMI (calculated as weight in kilograms divided by the square of the height in meters) was also considered because, in elderly individuals, it is an index of both fat and lean mass, and underweight is an acknowledged mortality risk factor in older age (16,17).…”
Section: Sociodemographic Lifestyle and Medical Informationmentioning
confidence: 99%